Nutrition Intake Among Stunting Toddler in Cimahi Urban Village - Anggi Yustiani Nuryanti; Ai Nurhayati; Cica Yulia (Universitas Pendidikan Indonesia (UPI), 2021)
Stunting was a state of height/length-for-age index below minus two standard deviations based on the WHO standard. Nutritional intake is one of the factors that directly influence the incidence of stunting. This study aims to analyze nutritional intake and consumption of nutrient sources in stunting infants in Cimahi Urban-Village. The study uses a cross-sectional design with descriptive research methods. The populations are 172 stunting toddlers using random sampling area and took 64 toddlers as respondent. Data collection was done through interviews using 24-hour food recall form and food frequency questionnaire. This study was carried out on December 6, 2018 - May 14, 2019. The results showed protein intake in the age group 1-3 years categorized as mild deficit and age group 4-5 years categorized as a severe deficit. Intake of fat, carbohydrates, calcium, phosphor, iron, vitamin A and vitamin C are categorized as severe deficits. Sources of nutrients that are often consumed include eggs consumed by age groups 1-3 years 5 times/week and age groups 4-5 years 4 times/week, oil consumed 1 time/day, rice consumed 2 times/day, milk consumed by age groups 1-3 years 5 times/week and the age group 4-5 years 3 times/week, chicken consumed 3 times/week and papaya consumed once/week. The recommendation is to hold assistance for parents of stunting toddler by posyandu cadres regarding the selection of food ingredients and the portion provided to suit the nutritional adequacy of the toddler.